Dioscin promotes autophagy by regulating the AMPK-mTOR pathway in ulcerative colitis. (4th March 2022) - Li, Han; Pang, Bo; Nie, Bin; Qu, Shifang; Zhang, Kuanxin; Xu, Jinxiu; Yang, Ming; Liu, Jie; Li, Shasha
Abstract: Background: Dioscin is reported to alleviate the dextran sodium sulfate (DSS)-induced ulcerative colitis (UC) in mice. Autophagy plays an anti-inflammatory role in UC. We herein aimed to explore the biological functions of dioscin in autophagy in UC. Methods: To explore the effects of dioscin on UC progression, a DSS-induced mouse model of UC was established. Body weight, disease activity index and macroscopic damage index scores were recorded for seven days. Hematoxylin & Eosin (HE) staining was used to stain colon sections and an BX53 microscope was prepared to observe pathological changes. The activities of glutathione, superoxidative dismutase, and malondialdehyde were determined by commercially available kits. Western blotting was performed to measure the protein levels of p-AMPK/AMPK, p-mTOR/mTOR and autophagy-related genes. Results: The DSS-induced colitis and oxidative stress in mice were ameliorated after dioscin treatment. Dioscin promoted the phosphorylation of AMPK to inhibit mTOR activation and facilitated autophagy in DSS-induced mice model of UC. Conclusion: Dioscin promotes autophagy by promoting the phosphorylation of AMPK to inhibit mTOR activation in ulcerative colitis.